Barack Obama Administration and the “war on drugs”: more continuity than change - Milani, Livia Peres (2017)
This article analyzes USA international drug policy and aims to understand if there were changes during Barack Obama administration. In order to do so, initially it presents a brief historical, then the focus is on Obama administration planning and finally it presents some observations about the police application. The partial conclusion is that there were no substantive alterations: international cooperation rests only in the security field.